A festa de Santa Luzia no espaço urbano de Porto Nacional, Tocantins - Amorim, Patrícia Castro de (Universidade Federal do Tocantins, 2023)
Each and every holy place demands and reinforces the emotional commitment of the devotee. The Festa de Santa Luzia in the urban space of Porto Nacional is an example of this manifestation of the sacred. The space lived by different social groups that ritualize their environment through myths and ancestral knowledge, small churches and popular religious festivals in urban societies. The objective of this research is to analyze the Festa de Santa Luzia, from the perspective of the geography of religion, structured in the research axis proposed by Zeni Rosendahl (2003), called “space and sacred place: experience, perception and symbolism”. It is a bibliographical research based on scientific articles, dissertations, theses and documents, as well as direct observation of the moments of the festival, its rituals, acts of devotion and symbolism. Catholic parties become spaces for socialization and belonging for residents, devotees and participants, involving human groups, religious or not, constituting an element that brings people together.